PENERAPAN APLIKASI SURAT MASUK DAN SURAT KELUAR PADA SMA NEGERI 1 SLIYEG INDRAMAYU - Dian Pramadhana; Robi Robiyanto; Rendi (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2022)
Letter is a means of communication to convey written information by one party to another and also serves as a reminder. In an educational institution, letters are very important, both outgoing and incoming letters that have different subjects. Therefore, in recording incoming and outgoing mail documents, it is necessary to archive documents as a form of good mail administration management. Archives are recorded information in any form of media, which are created, received and managed by an agency or individual in the context of carrying out activities or because of their legal obligations which have an important role as a source of information. One of the schools in the Indramayu area, especially SMA Negeri 1 Sliyeg, in managing letter archives still uses manuals recorded in ledgers and letter administration documents are stored in binders, so that it becomes less efficient in managing letter archive document administration. So that a computerized administration filing application for incoming and outgoing mail is made. In making applications for archiving incoming and outgoing letters, you can use the PHP programming language, data storage with a MySQL database, display applications with the Codeigniter Framework, and notebook or computer hardware. This application can save correspondence files with image file formats. Can make it easier to search for mail archives in the form of reports based on date, month, and year.